(untitled) (LEARNing Landscapes, 2018)
This study examined how the affordances of technologies in the blended learning affected teaching and learning activities. The study used mixed methods to examine whether the blended learning environments provided enhanced access to and more diverse data for teachers and students from which to make educational decisions. The study found that the technologies provided more diverse data to administrators, teachers, and students and allowed for flexible adaptations to virtual and face-to-face learning to meet students’ needs. The blended environments helped to create data cultures within the schools where educators used data to communicate and have an impact on instructional activities.